Increasing Availability of Exposure Therapy Through Intensive Group Treatment for Childhood Anxiety and OCD. Issue 5 (September 2018) - Whiteside, Stephen P. H.; Dammann, Julie E.; Tiede, Michael S.; Biggs, Bridget K.; Hillson Jensen, Andrea
Archival data were used to examine the feasibility of a 5-day, clinic-based, intensive exposure–based cognitive-behavioral group therapy for childhood anxiety disorders (CADs) and obsessive-compulsive disorder (OCD). Participants were 143 children (82 girls) aged 6 to 19 years ( M = 13.93 years, SD = 2.9 years) with CADs or OCD (or both) in 28 consecutive groups. Repeated-measures ANOVA in the subsample ( n = 57) with complete treatment data indicated positive change on all variables from pretreatment to posttreatment with few differences between CADs and OCD patients. Effect sizes were moderate to large for anxiety symptoms (parent reported = 0.74, child reported = 0.65) and impairment (parent reported = 1.02, child reported = 0.69). The intensive group protocol required fewer sessions and 36% fewer therapist-hours per patient than the individually administered protocol. The program increased treatment availability for families from diverse geographic areas ( M distance traveled to clinic = 407 miles, SD = 786.4 miles). These findings support further, well-controlled examination of the 5-day intensive group treatment protocol's efficacy and potential to increase availability of evidence-based exposure therapy.